2012
DOI: 10.3109/15360288.2012.702199
|View full text |Cite
|
Sign up to set email alerts
|

Nasogastric and Percutaneous Endoscopic Gastrostomy Tube Use in Advanced Head and Neck Cancer Patients: A Comparative Study

Abstract: To compare the efficacy of percutaneous endoscopic gastrostomy (PEG) and nasogastric (NGT) tube administration of enteral nutrition in head and neck cancer patients undergoing curative treatment, the authors conducted a prospective study to compare nutritional outcomes, complications, and patient satisfaction. PEG patients sustained significantly less reduction in nutritional parameters, measured at 6 weeks post insertion, as compared with NGT patients. There was also a statistically significant difference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 28 publications
0
63
1
Order By: Relevance
“…A total of 11 RCTs were included in the systematic review ( Table 2) (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Four trials explicitly stated they included patients with CVA complicated by dysphagia (36,38,41,42).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 RCTs were included in the systematic review ( Table 2) (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Four trials explicitly stated they included patients with CVA complicated by dysphagia (36,38,41,42).…”
Section: Resultsmentioning
confidence: 99%
“…NGT and PEG are the preferred strategies for enteral support, both of them have been demonstrated to be effective in achieving nutritional intake in HNC patients undergoing radiation therapy or concurrent radiochemotherapy [37,39,40]. NGT is easy to place but poorly tolerated for prolonged periods of feeding, because it is associated with frequent ulceration, esophageal reflux and general discomfort; however PEG is better tolerated, with a lower rate of acute complications if compared with other tubes, and quality of life is potentially improved [41].…”
Section: Discussionmentioning
confidence: 99%
“…NGT is easy to place but poorly tolerated for prolonged periods of feeding, because it is associated with frequent ulceration, esophageal reflux and general discomfort; however PEG is better tolerated, with a lower rate of acute complications if compared with other tubes, and quality of life is potentially improved [41]. The debate over the use of PEG and NGT in HNC patients is still open and it involves considerations about modality and timing of tube feeding positioning, particularly in patients whose nutritional status is intact [31,32,34,37,39,42]. Furthermore, best practice nutrition management guidelines recommend that specialized nutritionist should be part of the MDT, together with surgeon, radiotherapist and oncologist.…”
Section: Discussionmentioning
confidence: 99%
“…Another RCT comparing NGT (n=50) and gastrostomy (n=50) has been completed in India (Sadasivan, Faizal, & Kumar, 2012) however was not identified for inclusion in any of the systematic reviews. Whilst nutritional and QOL outcomes were better in the gastrostomy group the trial was deemed to be of negative quality.…”
Section: Tube Feeding: Optimal Type and Timingmentioning
confidence: 99%
“…A recent systematic review concluded that the optimal method of tube feeding remains unclear (Nugent, Lewis, & O'Sullivan, 2010b), although this was based on only one eligible randomised controlled trial (RCT) comparing the use of nasogastric tubes and gastrostomy tubes placed when required during treatment (Corry et al, 2008). Since then a new RCT has been published (Sadasivan et al, 2012) which supports the use of gastrostomy over nasogastric tubes, however the actual timing of the tube placement in relation to the treatment is unclear. Two further RCTs have compared proactive to reactive enteral feeding approaches, and while less weight loss is seen with the proactive approach, the differences are not statistically significant (Salas et al, 2009;Silander et al, 2012) There are benefits and disadvantages to both types of enteral feeding and their timing (Koyfman & Adelstein, 2012).…”
Section: Introductionmentioning
confidence: 99%